Introducing 'Neuromorphic Computing and Engineering'. Issue 1 (15th July 2021) - Indiveri, Giacomo
Abstract: The standard nature of computing is currently being challenged by a range of problems that start to hinder technological progress. One of the strategies being proposed to address some of these problems is to develop novel brain-inspired processing methods and technologies, and apply them to a wide range of application scenarios. This is an extremely challenging endeavor that requires researchers in multiple disciplines to combine their efforts and simultaneously co-design the processing methods, the supporting computing architectures, and their underlying technologies. The journal 'Neuromorphic Computing and Engineering' (NCE) has been launched to support this new community in this effort and provide a forum and repository for presenting and discussing its latest advances. Through close collaboration with our colleagues on the editorial team, the scope and characteristics of NCE have been designed to ensure it serves a growing transdisciplinary and dynamic community across academia and industry.